Pemidanaan Terhadap Pelaku Tindak Pidana Kekerasan Dalam Rumah Tangga Oleh Suami Terhadap Istri - Fitriya Wardhany, Nyimas Enny (Legalitas: Jurnal Hukum, 2024)
Domestic violence, especially that committed by husbands against their wives, is actually not a new thing. However, so far it has always been kept secret or covered up by the family, as well as by the victim himself or the family. Violence that occurs in the household contains something specific or special. The impact of violence experienced by wives can have psychological consequences such as anxiety, moodiness, depression, insecurity, loss of trust in their husbands, self-blame and so on. Physical consequences such as bruises, broken bones, physical disabilities, menstrual disorders, uterine damage, miscarriages, infectious diseases, psychomatic diseases and even death. Therefore, this article aims to analyse the punishment of perpetrators of domestic violence by husbands against wives.